Privacy view and target of differential privacy - Jingyu JIA; Chang TAN; Zhewei LIU; Xinhao LI; Zheli LIU; Tao ZHANG (网络与信息安全学报)
The study aimed to address the challenges in understanding the privacy goals of differential privacy by analyzing the privacy controversies surrounding it in various fields.It began with the example of data correlation and highlighted the differing perspectives among scholars regarding the targets of privacy protection.In cases where records in a dataset were correlated, adversaries can exploit this correlation to infer sensitive information about individuals, thereby sparking a debate on whether this violates privacy protection.To investigate the influence of privacy theories in the legal domain on defining privacy, two mainstream privacy theories in the computer field were examined.The first theory, limited access to personal information, focuses on preventing others from accessing an individual’s sensitive information.According to this theory, privacy mechanisms should aim to prevent adversaries from accessing a user’s actual information.In contrast, the second theory, control over personal information, emphasizes an individual’s right to communicate personal information to others.This theory suggests that the disclosure of personal information due to the relevance of others sharing data should not be considered a breach of privacy.Then the controversies of differential privacy were analyzed in the fields of computer science, social science, ethics and human-computer interaction due to their different understandings of privacy.By exploring the privacy concept of differential privacy from a multidisciplinary perspective, this study helps readers gain a correct understanding of the privacy viewpoint and goals of differential privacy while enhancing their understanding of the concept of “privacy” itself.